2022
DOI: 10.1038/s41420-022-00941-6
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial epithelial cells-derived exosomes deliver microRNA-30c to block the BCL9/Wnt/CD44 signaling and inhibit cell invasion and migration in ovarian endometriosis

Abstract: Endometriosis (EMs) is a benign gynecological disorder showing some tumor-like migratory and invasive phenotypes. This study intended to investigate the role of microRNA-30c (miR-30c) in EMs, which is involved with B-cell lymphoma 9 (BCL9), an activator of the Wnt/β-catenin signaling pathway. EMs specimens were clinically collected for determination of miR-30c and BCL9 expression. Exosomes were isolated from endometrial epithelial cells (EECs), and the uptake of exosomes by ectopic EECs (ecto-EECs) was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…As previously reported, PLAU and its receptor PLAUR were involved in regulating cell adhesion and promoting tumor cell migration [25,26], while c-Myc and AXL were associated with EMT, invasiveness, and migration [27,28]. Notably, CD44 was also upregulated in the disseminating leader cells and was reported to be associated with the functions of these genes (c-Myc, PLAU, PLAUR, and AXL) [29,30]. Moreover, from our previous study, CD44 switching was found to be related to the stemness and plasticity of cancer cells, showing the capability to give rise to collective invasion [8].…”
Section: The Acquisition Of Cd44 High State In Collective Detachmentmentioning
confidence: 71%
“…As previously reported, PLAU and its receptor PLAUR were involved in regulating cell adhesion and promoting tumor cell migration [25,26], while c-Myc and AXL were associated with EMT, invasiveness, and migration [27,28]. Notably, CD44 was also upregulated in the disseminating leader cells and was reported to be associated with the functions of these genes (c-Myc, PLAU, PLAUR, and AXL) [29,30]. Moreover, from our previous study, CD44 switching was found to be related to the stemness and plasticity of cancer cells, showing the capability to give rise to collective invasion [8].…”
Section: The Acquisition Of Cd44 High State In Collective Detachmentmentioning
confidence: 71%
“…Together, the evidence suggests endometriosis-specific stromal derived sEVs may contribute to disease progression. Recently, miR-30c encapsulated in sEVs derived from endometriotic epithelial cells was found to supress epithelial cell invasion and migration and attenuate endometriosis progression in a mouse model (94). These in vitro and in vivo studies indicate that the peritoneal microenvironment will likely contain a variety of sEVs, and that these sEVs may carry key factors instrumental in the pathogenesis of endometriosis.…”
Section: The Sev-mediated Crosstalk In the Peritoneal Microenvironmen...mentioning
confidence: 96%
“…Together, the evidence suggests endometriosis-specific stromal derived sEVs may contribute to disease progression. Recently, miR-30c encapsulated in sEVs derived from endometriotic epithelial cells was found to supress epithelial cell invasion and migration and attenuate endometriosis progression in a mouse model ( 94 ).…”
Section: Small Extracellular Vesicle-mediated Crosstalk In Tissue-spe...mentioning
confidence: 99%
“…The concentration of soluble CD44 in the serum and endometrial fluid of endometriosis patients was higher than that of healthy women [82]. In the mouse model of endometriosis, the role of epigenetic regulation of B-cell lymphoma 9 (BCL9)/Wnt/β-catenin/CD44 signaling pathway indicated, that exosomes containing miR-30c were able to inhibit invasion and migration of endometrial epithelial cells in ectopic lesions by blocking BCL9/Wnt/CD44 axis [83].…”
Section: Endometrium-derived Stem Cellsmentioning
confidence: 99%